Development of Spontaneous Activity in the Avian Hindbrain - Momose-Sato, Yoko; Sato, Katsushige (Frontiers in Neural Circuits, 2016)
Spontaneous activity in the developing central nervous system occurs before the brain responds to external sensory inputs, and appears in the hindbrain and spinal cord as rhythmic electrical discharges of cranial and spinal nerves. This spontaneous activity recruits a large population of neurons and propagates like a wave over a wide region of the central nervous system. Here, we review spontaneous activity in the chick hindbrain by focusing on this large-scale synchronized activity. Asynchronous activity that is expressed earlier than the abovementioned synchronized activity and activity originating in midline serotonergic neurons are also briefly mentioned.